The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/membranes10040059
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterisation of Deposit Layer during Milk Protein Microfiltration by Means of In-Situ MRI and Compositional Analysis

Abstract: Milk protein fractionation by microfiltration membranes is an established but still growing field in dairy technology. Even under cross-flow conditions, this filtration process is impaired by the formation of a deposit by the retained protein fraction, mainly casein micelles. Due to deposition formation and consequently increased overall filtration resistance, the mass flow of the smaller whey protein fraction declines within the first few minutes of filtration. Currently, there are only a handful of analytica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The influence of temperature on fouling layer structure and properties is studied very rarely, only data for skim milk filtration are available. For example [79], concluded from in situ MRI analysis of dead-end filtration of skim milk that deposit obtained at 45 • C (and mostly composed of casein micelles) is denser (i.e. more concentrated) than that obtained at 22 • C. This is in accordance with data presented in Fig.…”
Section: Discussion On Related Literature Data and Filtration Practicesupporting
confidence: 91%
See 2 more Smart Citations
“…The influence of temperature on fouling layer structure and properties is studied very rarely, only data for skim milk filtration are available. For example [79], concluded from in situ MRI analysis of dead-end filtration of skim milk that deposit obtained at 45 • C (and mostly composed of casein micelles) is denser (i.e. more concentrated) than that obtained at 22 • C. This is in accordance with data presented in Fig.…”
Section: Discussion On Related Literature Data and Filtration Practicesupporting
confidence: 91%
“…The importance of swelling for deposit erosion (Fig. 10) also suggests that external fouling could be more efficiently removed by not applying TMP when rinsing the membrane (this idea has already been voiced [77][78][79], also in the milk filtration literature [8]). This is because applied TMP counteracts the osmotic swelling pressure and reduces the swelling.…”
Section: Discussion On Related Literature Data and Filtration Practicementioning
confidence: 88%
See 1 more Smart Citation
“…The deposit formation of retained matter is an issue in all membrane systems, as reported for HFM [ 15 , 16 , 17 , 18 , 19 ], CTM [ 1 , 6 , 7 ], and SWM [ 9 , 11 ]; however, at different levels due to the different flow channel configurations. Deposit formation strongly impairs flux and the desired high whey protein mass flow, which is a key aspect in milk protein fractionation [ 7 ].…”
Section: Introductionmentioning
confidence: 98%
“…In previous studies, we have reported on MF-based milk protein fractionation by HFM [ 16 , 17 , 18 , 19 ], however with another perspective on fundamental aspects of deposit formation; therefore, small lab scale modules have been utilized. We also demonstrated that the length dependency in HFM is equal to that of CTM, and that the length-dependent pressure drop is responsible for inhomogeneous fouling along the HFM [ 19 ].…”
Section: Introductionmentioning
confidence: 99%